Nutritional profile and dietary intake of antioxidants of street runners - Pinho, Wendel Luiz; Pederneiras Rebelo da Silva, Adriana; Aniceto Santana, Levy (O Mundo da Saúde, 2016)
The regular practice of physical activity, associated with adequate nutrition, rich in antioxidant nutrients, provides protection to the body and reduces the risk of cell damage caused by excessive production of free radicals. The aim of this study was to evaluate the nutritional profile and dietary intake of antioxidants of street runners, members of a sports advisory group from the Federal District of Brasilia, Brazil. This is an analytical and descriptive cross-sectional study, carried out through a structured questionnaire and two adapted, contemplating the sociodemographic aspects, the knowledge about the importance and role of antioxidants in physical activity, and the frequency of dietary intake of antioxidants, along with anthropometric data extracted from the records of the participants from the company. The anthropometric profile showed that 80% of runners presented a Body Mass Index (BMI) above the normal range and 60% were outside the ideal body fat percentage. It was observed that 50% of the runners did not have enough information about the mechanisms of action of free radicals and antioxidants, and 95% presented a satisfactory level of knowledge concerning the importance of a healthy diet in the prevention of chronic diseases and premature aging. Among the antioxidants analyzed, a high intake of zinc and vitamin A and inadequate intake of selenium and flavonoids were observed. The results indicate an inadequate food intake of micronutrient antioxidants, and suggest the need for food education and individualized nutritional guidance aimed at the adoption of specific eating habits for the population studied.